2014
DOI: 10.3950/jibiinkoka.117.46
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Parotid Pleomorphic Adenoma Metastasis to Multiple Organs

Abstract: In January 2011, a 64-year-old woman who had undergone tumor resection for pleomorphic adenoma of the left parotid gland four times since her first operation in 1996 visited an orthopedist in our hospital complaining of pain in her right lower limb. Computed tomography (CT) of the whole body showed multiple tumors on the left parotid gland, right kidney, the sacrum, and both lungs. Biopsy of the sacral region and right nephrectomy were performed based on a clinical diagnosis of sacral and pulmonary metastases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…A systematic review showed that the most common sites for metastasis would be bones, lungs, and neck lymph nodes, respectively [10]. Very occasionally, however, PA metastases have been identified in the liver and kidneys [11,12]. On the same notion, parotid gland malignant tumours, such as acinic cell carcinoma, were also reported to metastasise to unusual sites, including the abdominal wall, cavernous sinus, and sternum [13,14].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review showed that the most common sites for metastasis would be bones, lungs, and neck lymph nodes, respectively [10]. Very occasionally, however, PA metastases have been identified in the liver and kidneys [11,12]. On the same notion, parotid gland malignant tumours, such as acinic cell carcinoma, were also reported to metastasise to unusual sites, including the abdominal wall, cavernous sinus, and sternum [13,14].…”
Section: Discussionmentioning
confidence: 99%